Epilepsy in young people : Portsmouth Symposium, June, 1986 - Ross, Euan M; Chadwick, David; Crawford, Robert (John Wiley & Sons, 1987)
Papers from a conference that focused on epilepsy in children and young adults. Intended for professional public.
A Wiley medical publication
Keywords: Adolescent; Epilepsy; Child; epilepsie; pediatrie; dítě; mladiství; neurologie